Determining feasible solutions of a multicriteria assignment problem (2010)
This paper presents an important research tool in operations research as it applies to a particular structure of the mullicritcria assignment problem. The paper addresses the problem of effectiveness of feasible solutions of a multicriteria assignment problem and this was done in two steps. In the first step, we determine whether or not a given feasible solution or a multicriteria assignment problem is a real efficient one. In the second step, if the feasible solution is not real efficient, we provide a real efficient solution that dominates that not real efficient solution, using our proposed method which consists of transforming the original problem into an assignment problem.